2002
DOI: 10.1038/sj.bdj.4801473
|View full text |Cite
|
Sign up to set email alerts
|

Crowns and other extra-coronal restorations: Try-in and cementation of crowns

Abstract: Having successfully negotiated the planning, preparation, impression and prescription of your crown, the cementation stage represents the culmination of all your efforts. This stage is not difficult, but a successful outcome needs as much care as the preceding stages. Once a restoration is cemented there is no scope for modification or repeat. You have to get it right first time. Decemented crowns often have thick layers of residual cement suggesting problems with either initial seating or cement handling. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 39 publications
(21 reference statements)
1
34
0
3
Order By: Relevance
“…The effective removal of the smear layer, exposure of collagen and opening of dentinal tubules promoted a better resin monomer (HEMA) penetration within the underlying dentin, thus creating a hybrid layer. Hybrid layer increases the surface energy and contributes to provide a better moisture of the dentin surface creating an interdiffusion zone between the cement and dentin matrix, which contributes to micromechanical retention, in addition to chemical adhesion to dentin (21,22,48). According to the previous research this study demonstrated the dentin bond strength of Fuji II LC using Clearfil SE Bond (contain hydrophilic monomers) was statistically higher than other treatments or no treatments (in the present study unconditioned specimens showed significantly lower bond strength results than all conditioned specimens).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective removal of the smear layer, exposure of collagen and opening of dentinal tubules promoted a better resin monomer (HEMA) penetration within the underlying dentin, thus creating a hybrid layer. Hybrid layer increases the surface energy and contributes to provide a better moisture of the dentin surface creating an interdiffusion zone between the cement and dentin matrix, which contributes to micromechanical retention, in addition to chemical adhesion to dentin (21,22,48). According to the previous research this study demonstrated the dentin bond strength of Fuji II LC using Clearfil SE Bond (contain hydrophilic monomers) was statistically higher than other treatments or no treatments (in the present study unconditioned specimens showed significantly lower bond strength results than all conditioned specimens).…”
Section: Discussionmentioning
confidence: 99%
“…The better bonding performance of RMGICs compared to conventional GICs could be due to their expected dual mechanism of adhesion (32). Resin cements are composites of a resin matrix, such as Bis-GMA or urethane dimethacrylate, and fine inorganic particles as filler (48). HEMA is an example of a hydrophilic primer, used to improve the infiltration of adhesive monomers into demineralised dentin by wetting the surface of collagen fibres and maintaining the collagen network in an expanded state by stiffening the collagen fibres (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive cement space has been attributed to a compromise in the mechanical durability of a restoration [88]. Excessive cement space also results in a loose fitting restoration that may affect the accuracy of seating the restoration, resulting in occlusal interferences, horizontal marginal discrepancies, and a loss in retention of the restoration [89]. Further, in cases with limited occlusal space, the final restoration thickness will be reduced, which increases the susceptibility of a mechanical failure.…”
Section: Computer-aided Production Streamsmentioning
confidence: 99%
“…All the Crowns were cemented to the teeth with type I glass ionomer cement (Fuji Plus, GC corporation, Leuven, Belgium, Europe). Cement was applied on the internal surface of the crowns with the help of spatula and was placed in position with a firm finger pressure [9]. The randomly selected remaining ten teeth in group B, C, D did not receive the crowns and served as subgroups B 1 , C 1 , D 1.…”
Section: Methodsmentioning
confidence: 99%